2020
DOI: 10.1182/blood.2018884940
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib monotherapy in patients with relapsed/refractory chronic lymphocytic leukemia: updated phase 2 results

Abstract: Therapeutic targeting of Bruton tyrosine kinase (BTK) has dramatically improved survival outcomes for patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). Acalabrutinib is an oral, highly selective BTK inhibitor that allows for twice-daily dosing due to its selectivity. In this phase 1b/2 study, 134 patients with relapsed/refractory CLL or SLL (median age, 66 years [range, 42-85 years]; median prior therapies, 2 [range, 1-13]) received acalabrutinib 100 mg twice daily for a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(173 citation statements)
references
References 54 publications
7
158
0
8
Order By: Relevance
“…The reported outcomes in patients with CLL are promising, with an ORR of 93% [including partial response with lymphocytosis (PRL)] and an 18-month PFS rate of 90% (95% CI, 83%-94%; ref. 18). The high selectivity of acalabrutinib may reduce the likelihood of off-target effects leading to toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported outcomes in patients with CLL are promising, with an ORR of 93% [including partial response with lymphocytosis (PRL)] and an 18-month PFS rate of 90% (95% CI, 83%-94%; ref. 18). The high selectivity of acalabrutinib may reduce the likelihood of off-target effects leading to toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The high selectivity of acalabrutinib may reduce the likelihood of off-target effects leading to toxicity. Although the results of a comparative trial between acalabrutinib and ibrutinib are not yet available, single-agent studies of acalabrutinib have shown lower rates of atrial fibrillation, hypertension, and arthralgias than similar studies with ibrutinib (18,19). In addition, the greater selectivity of acalabrutinib leads to less interference with antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC), as IL2-associated tyrosine kinase (ITK) is not inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Several novel oral targeted therapies are now available, including ibrutinib, acalabrutinib, and venetoclax. The choice of targeted therapy depends on several patient-and disease-related factors [45][46][47][48][49][50]. Ibrutinib and acalabrutinib generally require fewer clinic/laboratory visits at the time of treatment initiation compared with the venetoclax + obinutuzumab regimen.…”
Section: Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Acalabrutinib (ACP-196) is an oral, highly selective, irreversible and covalent BTK inhibitor which has been proven to inhibit off-target kinases, such as EGFR and ITK, to a lesser extent than ibrutinib [103,104]. In the phase I/II ACE-CL-001 trial (#NCT02029443), acalabrutinib was administered to 134 RR-CLL patients after at least one prior treatment regimen [105]. The ORR reached 85%, and inclusion of partial responses with lymphocytisis (PR-L) increased it to 93%, while the median PFS was not reached.…”
Section: Acalabrutinibmentioning
confidence: 99%